Bridgerton: when he was wicked - Quinn, Julia (London Piatkus (Hachette India), 2006)
'A veritable treat' Daily MailThe sixth novel in Julia Quinn's globally beloved and bestselling Bridgerton Family series, set in Regency times and now a series created by Shondaland for Netflix. Welcome to Francesca's story . . . ________________________________________In every life there is a turning point. A moment so tremendous, so sharp and breath-taking, that one knows one's life will never be the same. For Michael Stirling, London's most infamous bachelor, that moment came the first time he laid eyes on Francesca Bridgerton.After a lifetime of chasing women, of smiling slyly as they chased him, of allowing himself to be caught but never permitting his heart to become engaged, he took one look at Francesca Bridgerton and fell so fast and hard into love it was a wonder he managed to remain standing.Unfortunately for Michael, however, Francesca's surname was to remain Bridgerton for only a mere thirty-six hours longer - the occasion of their meeting was, lamentably, a supper celebrating her imminent wedding to his cousin . . .Find out why readers love Julia Quinn . . .'Light, pacy and full of feisty heroines' Guardian on the Bridgerton series'Julia Quinn's Bridgerton books take all of the classic tropes we know and love . . . and gives them a thoroughly modern twist. I can't focus on anything else' Stylist'Quinn is a master of historical romance' Entertainment Weekly'A smart, funny touch' Time Magazine'Like an episode of Downton Abbey mixed with a great rom-com' iBooks Best Books of March'Powered by a surfeit of dazzling wit and graced with a cast of unforgettable characters' Booklist'A romance readers will not want to put down . . . Hooray Julia!' Romance Reviews Today'Quinn writes delightfully fast-paced, funny, sparkling and bright romance' Romantic Times'The next best thing to Georgette Heyer' Gloss'Julia Quinn is one of the best historical romance novelists of our time' Heroes and Heartbreakers'Quinn excels in writing stories full of joy and delight, where laughter trembles on the edges' Happy Ever After'Full of wit, charm and smouldering attraction . . . an unputdownable story that I think romance fans will treasure' Harlequin Junkie'Quinn is incomparable.
Keywords: Fiction- English; Historical Fiction